Formulasi Krim Ekstrak Daun Kersen (Muntingia calabura L.) Dengan Variasi Kombinasi Span 60 dan Tween 80 Sebagai Emulgator - Metha Anung Anindhita; Catur Juni Arsanto (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
The ethanol extract of 1,04% Muntingia calabura L. folium has the effectiveness of healing burns. An emulgator is needed to maintain the stability of the cream formulation. Span 60 and tween 80 are non-ionic emulgators, non-toxic, non-irritating, and have low potential to couse hypersensitivity reactions. This research was conducted to determine the effect of the emulgator on physical properties and physical stability of Muntingia calabura L. folium extract cream and get the best formula from the cream. This study was compare the value of Hydrophile-Lipophile Balances (HLB) from a mixture of span 60 and tween 80, which is the HLB value of 5; HLB 6.5 and HLB 8. Evaluation of physical properties is done by testing organoleptic, homogeneity, pH, viscosity, adhesion, and ability to spread. Physical stability was assessed using the centrifugation method. The effect of emulgator variations was determined by One Way Anova testing using SPSS software. The best formula is chosen from those that fit the criteria for testing physical properties and which has the best stability. The results showed different variations in the combination of span 60 and tween 80 emulgators showed effects on adhesion and pH. Formula I with HLB value of 5 produces a cream formula with good physical properties and physical stability